Constitutional approach to municipal self-government (Discourse of Law and Administration, 2022)
The norms of constitutional law regulate the most important issues related to local government from the perspective of the functioning of the state. The basic unit of local government in the Polish legal system is the municipality. The constitution generally defines the tasks of self-government, its bodies and financing. In the case of the functioning of local self-governments, an important role is played by the principle of decentralization, i.e. shifting public tasks to the level closest to the citizen. The regulation of certain issues in the Constitution is a kind of security for local governments, guaranteeing their independence, consisting in undertaking public activities on their own account and at their risk.
Keywords: municipal self-government; decentralization; independence; tasks of self-government